(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Nanotechnology refers to a wide range of tools, technologies and applications consisting of microscopic particles approximately a few hundred nanometers in diameter.These extremely small particles (in their size) also have a set of physical and chemical properties and properties related to their surface, which are suitable for many uses and in different fields. This technology will address and find real solutions to issues related to medicine, energy, agriculture, and even environmental and military issues alike. Which will bring about a technological revolution Scientists interested in nanotechnology indicate that this great technology will contribute to finding solutions to some major global problems, such as providing clean drinking water to the entire population, whose numbers are increasing annually.